‘Agrarian Crisis’: Analysing the failure and developing strategies for sustainable development - Aggarwal, K P (Indian Farming, 2015)
Green revolution technologies led to rapid agricultural growth, eliminated famines and achieved food self sufficiency in 1990s. The growth in agriculture helped reduced poverty from 53% in 1977-78 to about 26% in 1999-00. Green revolution technologies fatigued with passage of time. The gains could not be sustained. There is increasing natural resources degradation, namely, the problem of waterlogging, salinity and over extraction of ground-water. Unbalanced fertilizer and pesticide use has led to soil nutrient imbalance.